Possibilities of usage meta-analysis method in economic research area = Możliwości stosowania meta analizy w badaniach ekonomicznych - Gondek, Anna (Zielona Góra: Faculty of Economics and Management Press)
The article presents the method of meta-analysis showing its essence, main elements, steps of carrying out research, as well as showing the advantages and disadvantages. In the support to available scientific bases of the source body of the literature, the author checked the economic studies, in which meta-analysis was used and divided them into twelve subject groups. Two group were the most numerous, they were: (1) macro-economics in such subject as development and growth economics, sustainable development, national accounts, public budgeting and finance and (2) management, especially about productivity, quality of human capital, organizational attitude, and widely understood competitiveness.
Keywords: metaanaliza; wielkość efektu; badania ekonomiczne; metodologia; meta-analysis; effect size; economic research area; methodology